Literature review methodology for scientific and information management, through its structuring and systematization (2014)
This paper presents a methodology to find, organize and analyze the information in any field of research, thereby facilitating the acquisition of the available information and the identification of the main authors, the number of publications per year, the main areas of work and the future trends in a proposal topic. It is also, showns an application of the methodology for the topic "Frequency Response Analysis with the transformer in service (FRA on-line)".